Application of ARPS–CMAQ modeling system for urban air pollutant emission abatement. Issue 4 (1st November 2013) - Wang, H.Y.; Li, J.B.; Guo, X.R.; Zhao, X.Y.; Cheng, S.Y.
Abstract : A coupled advanced regional prediction system  –  community multi-scale air quality (ARPS  –  CMAQ) modeling system was applied to develop an abatement strategy for air pollutant emission in the Handan region of the northern China. The system was evaluated by comparing the simulated concentrations of particulate matter less than 10  µm (PM10 ) with the observed results in the study area during the four representative months in 2005. A process of planning emission abatement was applied by gradually reducing PM10 emissions from the original GIS-based emission inventory until a modeling emission scenario was obtained under which the simulated PM10 concentrations could satisfy the desired air quality objective. The air quality objective was represented by an air quality guideline satisfaction ratio of 80% to reach a daily PM10 concentration of 150  µg/m 3 after the year 2010. The modeling system and results could provide sound basis for decision makers to develop an effective air quality management strategy.